New Treatment Horizons in Uveal and Cutaneous Melanoma - Daciana Elena Brănişteanu; Elena Porumb-Andrese; Vlad Porumb; Alexandra Stărică; Andreea Dana Moraru; Alin Codruț Nicolescu; Mihail Zemba; Cătălina Ioana Brănişteanu; George Brănişteanu; Daniel Constantin Brănişteanu (Life, 2023)
Melanoma is a complex and heterogeneous malignant tumor with distinct genetic characteristics and therapeutic challenges in both cutaneous melanoma (CM) and uveal melanoma (UM). This review explores the underlying molecular features and genetic alterations in these melanoma subtypes, highlighting the importance of employing specific model systems tailored to their unique profiles for the development of targeted therapies. Over the past decade, significant progress has been made in unraveling the molecular and genetic characteristics of CM and UM, leading to notable advancements in treatment options. Genetic mutations in the mitogen-activated protein kinase (MAPK) pathway drive CM, while UM is characterized by mutations in genes like GNAQ, GNA11, BAP1, EIF1AX, and SF3B1. Chromosomal aberrations, including monosomy 3 in UM and monosomy 10 in CM, play significant roles in tumorigenesis. Immune cell infiltration differs between CM and UM, impacting prognosis. Therapeutic advancements targeting these genetic alterations, including oncolytic viruses and immunotherapies, have shown promise in preclinical and clinical studies. Oncolytic viruses selectively infect malignant cells, inducing oncolysis and activating antitumor immune responses. Talimogene laherparepvec (T-VEC) is an FDA-approved oncolytic virus for CM treatment, and other oncolytic viruses, such as coxsackieviruses and HF-10, are being investigated. Furthermore, combining oncolytic viruses with immunotherapies, such as CAR-T cell therapy, holds great potential. Understanding the intrinsic molecular features of melanoma and their role in shaping novel therapeutic approaches provides insights into targeted interventions and paves the way for more effective treatments for CM and UM.